Pendekatan Pelayanan Kontekstual Melalui Musik Rohani Daerah Sub Suku Dayak Iban - Yabes Doma; Iskandar Iskandar; Apri Juverlis Clara Puri (Jurnal Teologi Kontekstual Indonesia, 2022)
The author discusses the contextual ministry approach through spiritual music in the language of the Iban Dayak tribe. In the Dayak Iban tribe, culture is still very fanatical, but that culture hasalso changed from generation to generation according to the times. Modern songs, local people find it difficult to understand the meaning of the song. That way, the authors are interested in using this opportunity to make an approach through the contextual service of the music of the Iban Dayak sub-tribe. The aim of the author is to approach the spiritual music of the Iban Dayak tribe. In this case, the research conducted by the author is using a descriptive approach with qualitative methods. By describing, explaining, describing what happened or studying what was the essence of the discussion. the author approaches by looking at the local culture. One of the approaches used by the writer to take this approach is to create spiritual songs in accordance with the language in the local area, so that the meaning of the songs created can be easily understood by the community. An example of the song is "Oh Bala Kaban", a traditional song from Dayak Ketungau Tengah.The author discusses the contextual ministry approach through spiritual music in the language of the Iban Dayak tribe. In the Dayak Iban tribe, culture is still very fanatical, but that culture hasalso changed from generation to generation according to the times. Modern songs, local people find it difficult to understand the meaning of the song. That way, the authors are interested in using this opportunity to make an approach through the contextual service of the music of the Iban Dayak sub-tribe. The aim of the author is to approach the spiritual music of the Iban Dayak tribe. In this case, the research conducted by the author is using a descriptive approach with qualitative methods. By describing, explaining, describing what happened or studying what was the essence of the discussion. the author approaches by looking at the local culture. One of the approaches used by the writer to take this approach is to create spiritual songs in accordance with the language in the local area, so that the meaning of the songs created can be easily understood by the community. An example of the song is "Oh Bala Kaban", a traditional song from Dayak Ketungau Tengah.